2018
DOI: 10.2116/analsci.18r001
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-based Point of Care Immunoassays for in vitro Biomedical Diagnostics

Abstract: In resource-limited settings, the availability of medical practitioners and early diagnostic facilities are inadequate relative to the population size and disease burden. To address cost and delayed time issues in diagnostics, strip-based immunoassays, e.g. dipstick, lateral flow assay (LFA) and microfluidic paper-based analytical devices (microPADs), have emerged as promising alternatives to conventional diagnostic approaches. These assays rely on chromogenic agents to detect disease biomarkers. However, limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…Although the cost of paper-based assays has decreased and their colorimetric output has undoubtedly improved owing to these modifications, there are still challenges that need to be addressed. (21,22,27,28) In laboratory-based assays, specimens must be labeled correctly with the patient ID, sample date, test type, and so forth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the cost of paper-based assays has decreased and their colorimetric output has undoubtedly improved owing to these modifications, there are still challenges that need to be addressed. (21,22,27,28) In laboratory-based assays, specimens must be labeled correctly with the patient ID, sample date, test type, and so forth.…”
Section: Discussionmentioning
confidence: 99%
“…(6)(7)(8)(9)(10)(11) These devices have been used in diverse medical and clinical applications. (12)(13)(14)(15)(16)(17)(18)(19) Along with their fabrication, different modifications have been proposed to make the output of microPADs more meaningful, (20)(21)(22) but a few issues such as readability still remain to be resolved fully. For example, after taking a biofluid sample (e.g., serum, urine, etc.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Au NPs and Ag NPs have characteristic optical properties in the visible region depending on their dispersion and aggregation in a liquid. 33,34 Therefore, the interaction between the NPs and glucose molecules leads to a color change, resulting in glucose level measurements with colorimetric approaches. Li et al reported a nonenzymatic method using gold nanostructures for glucose level detection forming a silver film via the silver mirror reaction (SMR).…”
Section: Introductionmentioning
confidence: 99%
“…(6)(7)(8)(9)(10)(11) These devices have been used in diverse medical and clinical applications. (12)(13)(14)(15)(16)(17)(18)(19) Along with their fabrication, different modifications have been proposed to make the output of microPADs more meaningful, (20)(21)(22) but a few issues such as readability still remain to be resolved fully. For example, after taking a biofluid sample (e.g., serum, urine, etc.…”
Section: Introductionmentioning
confidence: 99%